The Role of Islamic Law in the Development of the National Law System in Indonesia - Ratna Riyanti (IHSA Institute, 2021)
Islamic law provides a point of view in the national legal development system in Indonesia, the paradigm of Islamic law contains 2 dimensions, namely transcendental and horizontal, these two dimensions are placed in accordance with applicable norms and laws. The results of the study state that in the effort to apply Islamic law in Indonesia, there are relevant theories of thought so that Islamic law can be applied over time, first the Formalistic-Legalistic Theory of Thought, Second the Structuralistic Thought, Third Culturalistic thinking and finally the Applicative-Substantialistic Thought Theory.